SUICIDAL BEHAVIOR IN A GENERAL HOSPITAL AND THE KNOWLEDGE OF NURSING PROFESSIONALS: CROSS-SECTIONAL STUDY - Everly Maltaca Pypcak; Jaqueline Vieira Schultz; Márcio Roberto Paes; Rafaela Mildemberg; Edineia Miranda Machado; Miriam Aparecida Nimtz (Universidade Federal do Paraná, 2022)
Objective: to evaluate the knowledge of nursing professionals about suicidal behavior of patients in a general hospital. Method: cross-sectional study conducted in a general hospital in Paraná, Brazil, with 228 nursing professionals. Data were collected in the period between May 2019 and September 2020 by means of a structured instrument containing 20 sentences about suicidal behavior and its characteristics. Data were analyzed by descriptive statistical methods. Results: participants reported having experiences with patients whose behavior was suicidal (RMi=3.83); as for the statements that evaluated knowledge (RMi=2.73), they agreed on care and disagreed with the stigmatizing statements, demonstrating adequate conceptions about the phenomenon, however, it was identified that they need more knowledge to improve suicide preventive strategies (RMi=3.99). Conclusion: the study contributes to the construction of a comprehensive view regarding the care of patients in general hospital, encompassing the psycho-emotional needs, demystifying, and further promoting mental health.